1947
DOI: 10.2307/1538307
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption and Carbon Dioxide Elimination in Tetrahymena Geleii Furgason

Abstract: Unicellular organisms make excellent material for the study of various cellular phenomena. Tctrah\nncna t/clcii, a colorless holotrichous ciliate, is an exceptionally desirable organism for such physiological studies, mainly because it is readily grown in rather simple, sterile organic media. This organism contains cytochromes c, b, a, and possibly a._, and its oxygen consumption is inhibited by cyanide and carbon monoxide (Baker and Baumberger, 1941). It grows well at ordinary oxygen tensions, but is most pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1960
1960
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Our results are the first to illustrate a broad, general picture of the relationship between density and metabolic rate in protists. The literature is replete with studies on the metabolic rates of protists, and some have observed that the density of cells in a sample negatively affects the rate [13][14][15][16][17]. McCashland and Kronschnabel [17] suggested that competition for nutrients was the cause, foreshadowing our results here.…”
Section: Discussionsupporting
confidence: 53%
“…Our results are the first to illustrate a broad, general picture of the relationship between density and metabolic rate in protists. The literature is replete with studies on the metabolic rates of protists, and some have observed that the density of cells in a sample negatively affects the rate [13][14][15][16][17]. McCashland and Kronschnabel [17] suggested that competition for nutrients was the cause, foreshadowing our results here.…”
Section: Discussionsupporting
confidence: 53%
“…The metabolic rates recorded are due primarily to the metabolism of endogenous energy substrates which are not completely depleted even by three hours of starvation (lower pair of curves in Fig. The real value of these data to the experiments reported here lies in the fact that the resistance of the cells to the entry of succinate verifies the cellular vitality, for it has been shown (Seaman, 1953) that homogenates or cell-free extracts of T. pyriformis It has been stated frequently that the metabolic potential of T. pyriformis in culture decreases as the culture ages (Peters, 1929;Ormsbee, 1942;Pace and Lyman, 1947). The real value of these data to the experiments reported here lies in the fact that the resistance of the cells to the entry of succinate verifies the cellular vitality, for it has been shown (Seaman, 1953) that homogenates or cell-free extracts of T. pyriformis It has been stated frequently that the metabolic potential of T. pyriformis in culture decreases as the culture ages (Peters, 1929;Ormsbee, 1942;Pace and Lyman, 1947).…”
Section: Discussionmentioning
confidence: 51%
“…In the absence of nutrients, the limiting factor for the cell metabolism was oxygen or room. Pace and Lyman [13] had reported that the average oxygen consumption of the hungry Tetrahymena geleii cells in the different growth periods was all \400 lL h -1 per million cells. In the present study, the peak time for the maximum power output of Tetrahymena cells was \15 h. Making reference to 400 lL h -1 oxygen consumption per million cells, Tetrahymena cells oxygen consumption within 15 h was \2.25 mL, which was lower than the oxygen volume (about 3 mL) in the experimental ampoule bottles.…”
Section: T Thermophila Sb210 + T Thermophila Bf 1 P/mw T/minmentioning
confidence: 99%